Biotecnología agropecuaria para el desarrollo en América Latina: Oportunidades y retos - Trigo, Eduardo; Falconi, César; Falck-Zepeda, José B. (Inter-American Development Bank, 2010)
This document analyzes the state of research and development in agricultural biotechnology in Latin American and Caribbean countries, in the international context of development of the sector. Based on information obtained through surveys in 17 Latin American countries, a detailed description of the state of biotechnology in each country is presented. From the information on human and financial resources and their comparative analysis, we conclude, in general terms, that the levels of investment in most countries in the region are poor, and although countries with more advanced research systems, such as Brazil, Mexico and Argentina, allocate significant amounts of human and financial resources to biotechnology research in regional terms, these do not appear to be of the magnitude required to ensure results. With respect to the biotechnological techniques used in each country, it can be said that all countries in Latin America apply biotechnological techniques, but most of them are conventional. Finally, from the point of view of products, there is a clear contrast between what has to do with the production of knowledge and the activity of patenting, which could be an indirect indicator of the innovative potential of national systems and the region as a "user" of externally generated technologies.